Dinar and dirham: a study on the standard measure value of goods and services during the Prophet Muhammad’s (pbuh) era - Hilaluddin, Khaulah; M., Mohd Nazri (2018)
This study discusses the appropriateness of the gold dinar and silver dirham as a measure of the value of goods and services. According to Islamic history, this precious metal has been used as a measure of value long before the period of Prophet Muhammad (pbuh). So, the research question here is how the two metals had been applied as a measure of value at the time of Prophet Muhammad (pbuh). Qualitative data collection techniques and data analysis used in this study through written materials that the Prophet Muhammad himself (al-Hadith). Finally, the results showed that the two metals are protect the price value (non-inflation) and suitable as a standard measure of the value of goods and services of all time for the welfare and prosperity of all mankind.